Arsenic contamination : Bangladesh perspective - Ahmed, M. Feroze; ITN-Bangladesh (Network) (Dhaka : ITN-Bangladesh, Centre for Water Supply and Waste Management, 2003)
Contributed articles on arsenic poisoning and toxicology.
Includes bibliographical references.
Keywords: Arsenic -- Toxicology -- Bangladesh; Soils -- Arsenic content -- Bangladesh; Drinking water -- Arsenic content -- Bangladesh